The Role of Islamic Religious Education Teachers in Overcoming Student Delinquency - Muhammad Fachriiswantoro; Lismawati Lismawati (ARRUS Journal of Social Sciences and Humanities, 2023)
his study was conducted to determine the reality of student delinquency, its factors, and describe the efforts of Islamic Religious Education teachers in overcoming student delinquency. The method used in this study is a qualitative method with a phenomenological approach. Data was sourced from interviews with the Principal, Deputy Principal for Student Affairs, Islamic Religious Education teachers, and Counseling Guidance teachers. The results revealed that the reality of delinquency in SMP Negeri 6 Bukittingi students was divided into three levels, the first category involves mild delinquency, such as arriving late to school, dressing inappropriately, leaving class during instructional sessions, and neglecting assignments. The second category encompassed behaviors that disrupt the peace and security of others, including incidents such speeding on the street, engaging in fights, creating noise during instructional sessions, and smoking. The third category pertained to sexual delinquency, exemplified by behaviors such dating and socializing without boundaries. There are three factors causing student delinquency, namely: family environment, school, and community. The efforts of Islamic Religious Education teachers in overcoming student delinquency are preventive, repressive, and curative actions.